Secondary Syphilis Presenting as Glossodynia, Plaques en Prairie Fauchée, and a Split Papule at the Oral Commissure: Case Report and Review - Walter de Araujo Eyer-Silva; Maria Alessandra Leite Freire; Cecília Angelina Horta-Araujo; Guilherme Almeida Rosa da Silva; Jorge Francisco da Cunha Pinto; Fernando Raphael de Almeida Ferry (Case Reports in Medicine)
Syphilis has been coined “the great imitator” due to its extreme heterogeneity of presentation and mimicry of other conditions. Therefore, it is essential that physicians be familiar with the full spectrum of its manifestations. Syphilis may also lead to oral lesions that, occasionally, are unaccompanied by concomitant tegumentary findings. Such patients will pose unique diagnostic challenges. We report the case of a 45-year-old HIV-infected male patient in whom secondary syphilis presented with burning mouth and dysgeusia that progressed to glossodynia and odynophagia. Examination revealed painful, shallow erosions on the posterior aspect of the tongue, in a pattern of plaques en prairie fauchée. A painful split papule (fausse perlèche or false angular cheilitis) was also present in the left commissure. There were no cutaneous lesions. The oral lesions were considered highly suggestive of secondary syphilis. A novel VDRL assay (which was previously negative) yielded a titer of 1/128. Complete clinical remission was rapidly achieved after initiation of penicillin therapy. A comprehensive review of the literature on oral manifestations of syphilis is offered.